Creative Argumentation: When and Why People Commit the Metaphoric Fallacy - Ervas, Francesca; Ledda, Antonio; Ojha, Amitash; Pierro, Giuseppe Antonio; Indurkhya, Bipin (Frontiers in Psychology, 2018)
This article aims to understand when and why people accept fallacious arguments featuring metaphors (metaphoric fallacy) as sound arguments. Two experiments were designed to investigate, respectively, when and why participants fell into the metaphoric fallacy. In the first experiment, participants were provided with a series of syllogisms, presented in natural language, containing in their first premise either a lexically ambiguous, literal middle term or a metaphorical middle term, i.e. the term that “bridges” the first premise with the second premise, and ending with a true, false or plausible conclusion. For each argument they were asked to evaluate whether the conclusion followed from the premises. Results show that the metaphoric fallacy is harder to detect in case of arguments with plausible conclusion with a conventional metaphor rather than a novel metaphor as middle term. The second experiment investigated why participants considered the metaphoric fallacy with plausible conclusion as a strong argument. Results suggest that participants’ belief in the conclusion of the argument, independent from the premises, is a predictor for committing the metaphoric fallacy. We argue that a creative search for alternative reasons justifies participants’ falling into the metaphoric fallacy, especially when the framing effect of a metaphor covertly influences the overall reading of the argument. Thus, far from being a source of irrationality, metaphors might elicit a different style of reasoning in argumentation, forcing participants to find an alternative interpretation of the premises that guarantees the believed conclusion. In this process, conventional metaphors are revitalized and extended through the second premise to the conclusion, thereby entailing an overall metaphorical reading of the argument.